Rapid nongenomic modulation by neurosteroids of dendritic spines in the hippocampus: Androgen, oestrogen and corticosteroid. (18th February 2018) - Murakami, G.; Hojo, Y.; Kato, A.; Komatsuzaki, Y.; Horie, S.; Soma, M.; Kim, J.; Kawato, S.
Abstract: Memories are stored in synapses that consist of axon terminals and dendritic spines. Dendritic spines are postsynaptic structures of synapses and are essential for synaptic plasticity and cognition. Therefore, extensive investigations concerning the functions and structures of spines have been performed. Sex steroids and stress steroids have been shown to modulate hippocampal synapses. Although the rapid modulatory action of sex steroids on synapses has been studied in hippocampal neurones over several decades, the essential molecular mechanisms have not been fully understood. Here, a description of kinase‐dependent signalling mechanisms is provided that can explain the rapid nongenomic modulation of dendritic spinogenesis in rat and mouse hippocampal slices by the application of sex steroids, including dihydrotestosterone, testosterone, oestradiol and progesterone. We also indicate the role of synaptic (classic) sex steroid receptors that trigger these rapid synaptic modulations. Moreover, we describe rapid nongenomic spine modulation by applying corticosterone, which is an acute stress model of the hippocampus. The explanations for the results obtained are mainly based on the optical imaging of dendritic spines. Comparisons are also performed with results obtained from other types of imaging, including electron microscopic imaging. Relationships between spine modulation and modulation of cognition are discussed. We recognise that most of rapid effects of exogenously applied oestrogen and androgen were observed in steroid‐depleted conditions, including acute slices of the hippocampus, castrated male animals and ovariectomised female animals. Therefore, the previously observed effects can be considered as a type of recovery event, which may be essentially similar to hormone replacement therapy under hormone‐decreased conditions. On the other hand, in gonadally intact young animals with high levels of endogenous sex hormones, further supplementation of sex hormones might not be effective, whereas the infusion of blockers for steroid receptors or kinases may be effective, with respect to suppressing sex hormone functions, thus providing useful information regarding molecular mechanisms.